BoSapient®, a Cell-Based BoNT-A Potency Assay Optimized for Manual and Semi-Automated Procedures - F. Mark Dunning; Sara Hendrickson; Serena Wolfe; Dan Harding; Theresa Geurs; Timothy M. Piazza; Thomas A. Little; Ward C. Tucker (Toxicon, 2026)

A comparative analysis of detailed and reduced CFD approaches to model wire-wrapped fuel bundles for LMFBRs applications - O. Halim; F. Galleni; N. Forgione; I. Di Piazza; A. Pucciarelli (Annals of Nuclear Energy, 2025)

Loss-of-heat-sink transient simulation with RELAP5/Mod3.3 code for the ATHENA facility - T. Del Moro; F. Giannetti; P. Cioli Puviani; I. Di Piazza; D. Diamanti; M. Tarantino (Annals of Nuclear Energy, 2025)

The efficacy of cognitive stimulation, cognitive training, and cognitive rehabilitation for people living with dementia: a systematic review and meta-analysis - Alice Paggetti; Ylenia Druda; Francesco Sciancalepore; Francesco Della Gatta; Antonio Ancidoni; Nicoletta Locuratolo; Paola Piscopo; Luca Vignatelli; Luciano Sagliocca; Antonio Guaita; Piero Secreto; Andrea Stracciari; et al. (GeroScience, 2024)
Cognition-oriented treatments (COTs) are a group of non-pharmacological treatments aimed at maintaining or improving cognitive functioning. Specific recommendations on the use of these interventions in people living with dementia (PLwD) are included in the Italian Guideline on the Diagnosis and Treatment of Dementia and Mild Cognitive Impairment, developed by the Italian National Institute of Health. This systematic review and meta-analysis, based on the GRADE methodology, is part of the guideline. Considered outcomes included the cognitive functions, quality of life, and functional abilities of PLwD, taking into account disease severity, modality and system of delivery, and form of the intervention. The effectiveness of these interventions on caregivers’ outcomes was also assessed. Both group and individual cognitive stimulation were reported as effective in supporting cognitive functions in PLwD at any degree of severity. Individual cognitive training and group cognitive training were reported as effective in improving global cognitive functions in people with mild dementia. Cognitive rehabilitation appeared to be effective only in improving the functional abilities of people with mild dementia. Cognitive rehabilitation appeared to be the most effective in improving caregivers’ outcomes, with results suggesting a reduction in care burden. The observed differences in the effectiveness of these interventions in people with different disease severity can be explained by the intrinsic characteristics of each intervention. Despite the large number of available studies, a high clinical, statistical, and methodological heterogeneity was observed. More methodologically rigorous studies are needed to clarify the effectiveness of each protocol and modality of intervention.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Sensitive and Accurate Detection of Botulinum Neurotoxin Types A, B, E, and F From Diverse Food Samples Using the BoLISA® Assay - F. Mark Dunning; Timothy M. Piazza; Ward C. Tucker (Toxicon, 2024)

Carotid artery stenting during endovascular thrombectomy for acute ischemic stroke with tandem occlusion: the Italian Registry of Endovascular Treatment in Acute Stroke - Fabrizio Sallustio; Giovanni Pracucci; Manuel Cappellari; Valentina Saia; Alfredo Paolo Mascolo; Federico Marrama; Roberto Gandini; Giacomo Koch; Marina Diomedi; Federica D’Agostino; Alessandro Rocco; Valerio Da Ros; et al. (Acta Neurologica Belgica, 2023)

Craniectomies for Dogs With Skull Multilobular Osteochondrosarcoma Using the Misonix Bone Scalpel: Cadaveric Evaluation and Retrospective Case Series - Alexander M. Piazza; Jonathan F. McAnulty; Peter Early; Julien Guevar (Topics in Companion Animal Medicine, 2023)

A first-of-its-kind multi-model convection permitting ensemble for investigating convective phenomena over Europe and the Mediterranean - Erika Coppola; Stefan Sobolowski; E. Pichelli; F. Raffaele; B. Ahrens; I. Anders; N. Ban; S. Bastin; M. Belda; D. Belusic; A. Caldas-Alvarez; R. M. Cardoso; et al. (Climate Dynamics, 2020)

Regional climate downscaling over Europe: perspectives from the EURO-CORDEX community - Daniela Jacob; Claas Teichmann; Stefan Sobolowski; Eleni Katragkou; Ivonne Anders; Michal Belda; Rasmus Benestad; Fredrik Boberg; Erasmo Buonomo; Rita M. Cardoso; Ana Casanueva; Ole B. Christensen; et al. (Regional Environmental Change, 2020)
The European CORDEX (EURO-CORDEX) initiative is a large voluntary effort that seeks to advance regional climate and Earth system science in Europe. As part of the World Climate Research Programme (WCRP) - Coordinated Regional Downscaling Experiment (CORDEX), it shares the broader goals of providing a model evaluation and climate projection framework and improving communication with both the General Circulation Model (GCM) and climate data user communities. EURO-CORDEX oversees the design and coordination of ongoing ensembles of regional climate projections of unprecedented size and resolution (0.11° EUR-11 and 0.44° EUR-44 domains). Additionally, the inclusion of empirical-statistical downscaling allows investigation of much larger multi-model ensembles. These complementary approaches provide a foundation for scientific studies within the climate research community and others. The value of the EURO-CORDEX ensemble is shown via numerous peer-reviewed studies and its use in the development of climate services. Evaluations of the EUR-44 and EUR-11 ensembles also show the benefits of higher resolution. However, significant challenges remain. To further advance scientific understanding, two flagship pilot studies (FPS) were initiated. The first investigates local-regional phenomena at convection-permitting scales over central Europe and the Mediterranean in collaboration with the Med-CORDEX community. The second investigates the impacts of land cover changes on European climate across spatial and temporal scales. Over the coming years, the EURO-CORDEX community looks forward to closer collaboration with other communities, new advances, supporting international initiatives such as the IPCC reports, and continuing to provide the basis for research on regional climate impacts and adaptation in Europe.

Ecology and diversity of Cortinarius species (Agaricales, Basidiomycota) associated with Quercus ilex L. in the Mediterranean area of Liguria (North-western Italy) - M. Zotti; E. Ambrosio; S. Di Piazza; A. Bidaud; F. Boccardo; M. Pavarino; M. G. Mariotti; A. Vizzini (Plant Biosystems, 2014)

Deposition in St. Mark's Basilica of Venice - E. Morabito; E. Zendri; R. Piazza; R. Ganzerla; S. Montalbani; E. Marcoleoni; F. Bonetto; A. Scandella; C. Barbante; A. Gambaro (Environmental Science and Pollution Research, 2013)

Fungal biodiversity and in situ conservation in Italy - G. Venturella; E. Altobelli; A. Bernicchia; S. Di Piazza; D. Donnini; M. L. Gargano; S. P. Gorjòn; V. M. Granito; A. Lantieri; D. Lunghini; A. Montemartini; F. Padovan; et al. (Plant Biosystems, 2011)

Swimming speed alteration of larvae of Balanus Amphitrite as a behavioural end-point for laboratory toxicological bioassays - M. Faimali; F. Garaventa; V. Piazza; G. Greco; C. Corrà; F. Magillo; M. Pittore; E. Giacco; L. Gallus; C. Falugi; G. Tagliafierro (Marine Biology, 2006)

A new photodegradable molecule as a low impact ballast water biocide: efficacy screening on marine organisms from different trophic levels - M. Faimali; F. Garaventa; E. Chelossi; V. Piazza; O.D. Saracino; F. Rubino; G.L. Mariottini; L. Pane (Marine Biology, 2006)

Anticooperativity in diffusion-controlled reactions with pairs of anisotropic domains: a model for the antigen–antibody encounter - F. Piazza; P. De Los Rios; D. Fanelli; L. Bongini; U. Skoglund (European Biophysics Journal, 2005)

X-ray absorption near-edge spectroscopy of transferrins: a theoretical and experimental probe of the metal site local structure - F. Boffi; I. Ascone; S. Della Longa; M. Girasole; G. Yalovega; A. V. Soldatov; A. Varoli-Piazza; A. Congiu Castellano (European Biophysics Journal, 2003)

Study of the addictive potential of modafinil in naive and cocaine-experienced rats - Deroche-Gamonet V.; Darnaudéry M.; Bruins-Slot L.; Piat F.; M. Le Moal; Piazza P. (Psychopharmacology, 2002)

Cryptococcus neoformans Infection in a Cohort of Italian AIDS Patients: Natural History, Early Prognostic Parameters, and Autopsy Findings - S. Antinori; L. Galimberti; C. Magni; A. Casella; L. Vago; F. Mainini; M. Piazza; M. Nebuloni; M. Fasan; C. Bonaccorso; G. Vigevani; A. Cargnel; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Comparative XANES study of serotransferrin and ovotransferrin at Cu K-edge: evidence of interactions among the metal sites - F. Boffi; I. Ascone; A. Varoli Piazza; M. Girasole; S. Della Longa; A. Giovannelli; A. Congiu Castellano (BioMetals, 2000)

The fate of murine hepatitis virus (MHV-3) after intravenous injection into susceptible mice - M. Piazza; G. Pane; F. Ritis (Archives of Virology, 1967)